2011
DOI: 10.1007/s11250-011-9893-2
|View full text |Cite
|
Sign up to set email alerts
|

PCR test for detecting Taenia solium cysticercosis in pig carcasses

Abstract: Polymerase chain reaction (PCR) test was employed to detect Taenia solium DNA in muscle lesions for validation of the meat inspection results of slaughtered pigs. Two sets of oligonucleotide primers, one targeted against the large subunit rRNA gene (TBR primers) and the other targeted against cytochrome c oxidase subunit 1 gene (Cox1 primers) of T. solium were used in this study. On reactivity in PCR test, the TBR primers and the Cox1 primers yielded products of 286 and 984 bp, respectively, in cysticercosis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…The PCR conditions were optimised using different temperature setups for annealing and concentrations of No. 05102015-00063-EN 5/16 reagents/chemicals as per previously described methods (22,23…”
Section: Polymerase Chain Reaction Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR conditions were optimised using different temperature setups for annealing and concentrations of No. 05102015-00063-EN 5/16 reagents/chemicals as per previously described methods (22,23…”
Section: Polymerase Chain Reaction Amplificationmentioning
confidence: 99%
“…Some studies have reported similar detection limits (23) whereas others have reported lower detection limits (1 pg) for TBR primers(19). Higher detection limits (1 ng) for JB primers have also been reported(23). The variation in the detection limits of PCR using TBR and JB primers may be attributed to differences in sample preparation and DNA extraction methods.…”
mentioning
confidence: 97%
“…The PCR III method yielded products only when annealing temperature was lowered by 2 C (from 59 C to 57 C) with reference to original procedure described by Sredeevi et al (16). In such conditions, there were no nonspecific reactions with three other Taenidae parasites.…”
Section: Discussionmentioning
confidence: 99%
“…The method was based on the procedure described by Sreedevi et al (16), which was modified during investigation. Target sequence in this method encodes the T. solium cytochrome c oxidases ubunit 1 gene -this sequence was previously published by Yamasaki et al (18).…”
Section: Methodsmentioning
confidence: 99%
“…Primarily, PCR tests have been applied to identify doubtful T. solium cystic lesions in pork meat and also to confirm the results obtained during inspection of meat from slaughtered pigs (41). Karamon et al (27) optimised three different PCR assays developed previously for identification of T. solium (32,41,47). Comparison of the effectiveness of these PCRs revealed that the most sensitive and specific one is nested PCR by Mayta et al (32).…”
Section: Diagnostics Of Porcine Cysticercosismentioning
confidence: 99%